2012
DOI: 10.4171/jems/305
|View full text |Cite
|
Sign up to set email alerts
|

Hereditarily Hurewicz spaces and Arhangel'skiĭ sheaf amalgamations

Abstract: A classical theorem of Hurewicz characterizes spaces with the Hurewicz covering property as those having bounded continuous images in the Baire space. We give a similar characterization for spaces X which have the Hurewicz property hereditarily.We proceed to consider the class of Arhangel'skiȋ α1 spaces, for which every sheaf at a point can be amalgamated in a natural way. Let Cp(X) denote the space of continuous real-valued functions on X with the topology of pointwise convergence. Our main result is that Cp(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Moreover, by A. Dow [15] Scheepers' Conjecture holds in the Laver model constructed by A. Laver [24], see e.g. [28,44] or [4].…”
Section: Upper Semicontinuous Functionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, by A. Dow [15] Scheepers' Conjecture holds in the Laver model constructed by A. Laver [24], see e.g. [28,44] or [4].…”
Section: Upper Semicontinuous Functionsmentioning
confidence: 95%
“…We summarize essential results about these properties, for more see [18,6,34,3,35,44]. For a definition of an S 1 (Γ, Γ)-space see the end of this section.…”
Section: Preliminaries and Basic Notionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1.4 [22]. For a perfectly normal and strongly zero-dimensional space X, the following are equivalent.…”
Section: Introductionmentioning
confidence: 88%
“…Gerlits, Nagy [11] and Scheepers [19] showed that properties (α 2 ) and (α 4 ) are equivalent for C p (X). Tsaban and Zdomskyy [22] showed that if X is perfectly normal and strongly zero-dimensional (i.e., X is a space satisfying that every open subset is the union of countably many clopen sets in X), then properties (α 1 ) and (α 3/2 ) are equivalent for C p (X). Indeed, they proved the following.…”
Section: Introductionmentioning
confidence: 99%